2018
DOI: 10.1007/s13197-018-3284-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of gluten-free cereal bar for gluten intolerant population by using quinoa as major ingredient

Abstract: The present study was carried out to develop gluten free cereal bars for gluten intolerant population. The cereal bar was formulated using dry raw materials (quinoa, brown rice, flaxseed and dry fruits) and binding agents (honey). Honey was added as a sweetener and binding agent. The raw materials were assessed for physico-chemical parameters such as moisture, ash, crude protein and fat content and the functional parameters such as antioxidant activity, total phenolic content and β-carotene. Dry heat treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
1
23
1
6
Order By: Relevance
“…Lastly, the amount of proteins obtained from cereal bars containing nanosuspension from seed coats of pinhão exhibits values three times higher than the available commercial cereal bars and, although they have lower values than protein bars used by athletes, the advantage comes from the cheaper cost in producing them. Even though pinhão seed coat possess protein in its nutrients (1.8 g/100 g of dried seed coat), and studies have shown that seed coats tends to also present higher protein values (Kalpanadevi & Mohan, 2013), the increase may be due to the specific ingredients—flaxseed and skim milk powder—that helped contributed to this quantity (Kaur, Ahluwalia, Sachdev, & Kaur, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the amount of proteins obtained from cereal bars containing nanosuspension from seed coats of pinhão exhibits values three times higher than the available commercial cereal bars and, although they have lower values than protein bars used by athletes, the advantage comes from the cheaper cost in producing them. Even though pinhão seed coat possess protein in its nutrients (1.8 g/100 g of dried seed coat), and studies have shown that seed coats tends to also present higher protein values (Kalpanadevi & Mohan, 2013), the increase may be due to the specific ingredients—flaxseed and skim milk powder—that helped contributed to this quantity (Kaur, Ahluwalia, Sachdev, & Kaur, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Research on cereal bars in recent years has mostly been based on gluten‐free formulations (Kaur et al. ) and on the development of bars with several new ingredients (Martinelli et al. ), focusing on stability during storage, sensory properties and several functionalities, such as delivering satiety or inhibiting rises in blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cereal bars are versatile in their formulation and can be designed to address different trends in consumer choices for food intake (sportification, protein, healthiness and snackification) (Kriegl, 2016). Research on cereal bars in recent years has mostly been based on gluten-free formulations (Kaur et al 2018) and on the development of bars with several new ingredients (Martinelli et al 2018), focusing on stability during storage, sensory properties and several functionalities, such as delivering satiety or inhibiting rises in blood glucose levels. Studies dealing with the influence of the labeling of this kind of product on consumer perceptions are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Other technological applications of quinoa flour involve gelation, water-holding and foaming capacity (Abugoch et al, 2008). This technological versatility of quinoa supports its excellent capacity to substitute wheat flour in the elaboration of cookies (Jan, Panesar, & Singh, 2018) and other bakery products (Garcia et al, 2018), gluten-free pasta (Lorenzo, Sosa, & Califano, 2018), cereal bars (Kaur, Ahluwalia, Sachdev, & Kaur, 2018), and even its use as milk replacer (Jeske, Zannini, Cronin, & Arendt, 2018). However, the high content of sensitive compounds (i.e., unsaturated fatty acids, proteins, antioxidants, vitamins, starch) represents a great challenge for technological processes, limiting the stability of the obtained products.…”
Section: Introductionmentioning
confidence: 90%